Yo, robot - Asimov, Isaac, 1920-1992 (Pocket Edhasa., 2010)
In this collection Asimov sets out the principles of robot behavior known as the Three Laws of Roboticsm, which are exemplified in a series of stories of robots gone mad, mind-reading robots, robots with a sense of humor, robot politicians, and robots who secretly run the world.